2018
DOI: 10.6007/ijarbss/v8-i5/4436
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Family Business in Malaysia: Development, Culture and the Family Business Philosophy

Abstract: Although there has been an emerging field of research on Chinese family firms recently, the level at which Malaysia Chinese family firms were studied is surprisingly far below the observed realities surrounding this type of businesses including their scope of involvement and achievements. This paper, which is built on the existing literature on the topic of Chinese family firms in Malaysia, discusses the development of these firms and the role of Chinese culture and the family business philosophy in shaping th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Malaysians are known for their strong family connections and trust among family circles and peers (35). Lange et al (29) reported similar findings where young consumers trusted their family members as credible sources of food safety knowledge.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Malaysians are known for their strong family connections and trust among family circles and peers (35). Lange et al (29) reported similar findings where young consumers trusted their family members as credible sources of food safety knowledge.…”
Section: Resultsmentioning
confidence: 90%
“…Lange et al (29) reported similar findings where young consumers trusted their family members as credible sources of food safety knowledge. A prevalent practice among local Malaysian culture is distrust of strangers and people not belonging to their circle (35). This explains the level of distrust of food safety news shared by strangers.…”
Section: Resultsmentioning
confidence: 99%
“…Attracting visitors from inside the country is a key concern of many governments. Mosbah& Saleh (2014) pointed out that a priority is given to specific destinations targeting at internal visitors. According to Chu (2018), given that many countries around the world have placed such emphasis on the tourism industry, strategists exert an effort to studyvisitors'decision-making process with regard to their chosen destinations.…”
Section: Introductionmentioning
confidence: 99%
“…However, after the signing of a partnership agreement with the European Union (EU), the definition was aligned with the EU’s SME definition, which is ‘any enterprise that produces goods and services and at the same time employs 1 to 250 people and whose annual turnover does not exceed DZD 2 billion or whose total assets do not exceed DZD 500 million’ (see Table 1). The categories of enterprises, including micro and SMEs, are classified based on three criteria: number of employees, total sales and total assets (Atil 2009; Mosbah and Debili 2014). According to Mosbah and Debili (2014), the structure of Algerian SMEs has significantly facilitated the economic transition process by allowing local entrepreneurs a 75% share of business capital.…”
Section: Introductionmentioning
confidence: 99%